Problems of Accounting Computerization - Palubinskienė, Stasė (Ekonomika, 1997)
The article discusses the reasons for the insufficient use of computers for accounting automation. The main reason for the inefficiency of the computeraided accounting system is the usage of hand-aided accounting technologies. This causes an insufficient use of technical possibilities of modem computers, a low level of automation of data processing in accounting, and restrictions of information usage for management and control.The other factor influencing the effectiveness of the computeraided accounting system is the organized form of computers' usage.In this paper, the author suggests that big enterprises Connect into local area network computers and that small enterprises and private firms process their accounting data in centralized computer centers.One of the most urgent measures for increasing the effectiveness of the computeraided accounting system is the integration of cash-free transaction processing among enterprises and banks, where their accounts are, because it allows for the elimination of double input of the same data.